2021
DOI: 10.1051/bsgf/2020038
|View full text |Cite
|
Sign up to set email alerts
|

Control of inherited accreted lithospheric heterogeneity on the architecture and the low, long-term subsidence rate of intracratonic basins

Abstract: Intracratonic basins tend to subside much longer than the timescale predicted by thermal relaxation of the lithosphere. Many hypotheses have been suggested to explain their longevity, yet few have been tested using quantitative thermo-mechanical numerical models, which capture the dynamic of the lithosphere. Lithospheric scale geodynamic modelling preserving the tectono-stratigraphic architecture of these basins is challenging because they display only few kilometres of subsidence over 1000 of km during time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…The succession of compressional events to a rift extension occurred also in other ICBs, such as those of North America, (e.g., Klein and Hsui, 1987) and Australia, where the phases of intracontinental orogeny lead to the separation of the Centralian Superbasin of Australia in four main basins (Officer, Amadeus, Ngalia and Georgina basins), between 600 and 300 Myr (e.g., Lindsay, 2002). It has been demonstrated that small variations of the far field stresses cause period of subsidence acceleration, deceleration and even inversion (Perron et al, 2020). Therefore, periodic changes in far field tectonic can significantly complicate the tectono-stratigraphic architecture of the basins, by introducing stratigraphic unconformities between different neighboring basins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The succession of compressional events to a rift extension occurred also in other ICBs, such as those of North America, (e.g., Klein and Hsui, 1987) and Australia, where the phases of intracontinental orogeny lead to the separation of the Centralian Superbasin of Australia in four main basins (Officer, Amadeus, Ngalia and Georgina basins), between 600 and 300 Myr (e.g., Lindsay, 2002). It has been demonstrated that small variations of the far field stresses cause period of subsidence acceleration, deceleration and even inversion (Perron et al, 2020). Therefore, periodic changes in far field tectonic can significantly complicate the tectono-stratigraphic architecture of the basins, by introducing stratigraphic unconformities between different neighboring basins.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the modelled fields, depending on the topography and density variations, induced by the mantle upwelling, could reproduce a trend of anomalies similar to that observed, but not the shape of all the small anomalies related to the sediments distribution and local heterogeneities of the basement, present already before the syn-rift phase or acquired during the following tectonic events. The basement heterogeneity can have played a significant role on the long-term subsidence of the ICBs, by resisting local isostatic re-equilibration (Perron et al, 2020) and thus should be included in the future numerical models to reproduce the short wave-length of the basement depth variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the Peninsula Sandstone characterizes a proximal setting where the succession wedge-out onto basement rocks at the scale of a few tens of km, as should also occurred to the south of the Ennedi. Note that the relatively limited thickness (<200 m) of the Ordovician in the study area might not be solely a signature of the proximality of the Ennedi, as along-strike thickness changes reflecting subsidence/uplift trends controlled by basement heterogeneities [Nkono et al, 2018] could also have played a significant role, as recognized elsewhere throughout the platform [Klitzsch, 1970, Perron et al, 2021.…”
Section: The Preglacial Successionmentioning
confidence: 95%
“…And therefore, tectonic events in North Africa and Middle East during this period were probably independent of the Caledonian Orogeny. Instead, the origins of the Late Silurian event and related low uplift within the African basins were interpreted as the result of the following: (1) intra‐plate stress linked to far‐field stresses (Perron, 2019), which is probably from the collision front of Iapetus Ocean closure (Fekirine & Abdallah, 1998) or rifting along the Gondwana margin (Boote & Clark‐Lowes, 1998); and (2) heterogeneity of accretionary continental lithosphere equilibration together with periodic changes in far‐field tectonic forcing from extension to compression (Perron et al, 2021).…”
Section: Basin Patterns Before and After The Hercynian Orogeny: From ...mentioning
confidence: 99%